2010
DOI: 10.1590/s0103-64402010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro human gingival fibroblast seeding on acellular dermal matrix

Abstract: The acellular dermal matrix (ADM) was introduced in periodontology as a substitute for the autogenous grafts, which became restricted because of the limited source of donor's tissue. The aim of this study was to investigate, in vitro, the distribution, proliferation and viability of human gingival fibroblasts seeded onto ADM. ADM was seeded with human gingival fibroblasts for up to 21 days. The following parameters were evaluated: cell distribution, proliferation and viability. Results revealed that, at day 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 18 publications
4
32
0
1
Order By: Relevance
“…Similarly to observations made by Ng et al, Rodrigues et al, and Sorrel and Caplan, fibroblast inhabiting the surface of the studied ADMs did not migrate inwards toward the ECM structure. The reasonable explanation of this phenomenon may be attributed to dense, strict, and highly cross‐linked collagen structure of ADM .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly to observations made by Ng et al, Rodrigues et al, and Sorrel and Caplan, fibroblast inhabiting the surface of the studied ADMs did not migrate inwards toward the ECM structure. The reasonable explanation of this phenomenon may be attributed to dense, strict, and highly cross‐linked collagen structure of ADM .…”
Section: Discussionsupporting
confidence: 89%
“…The histological image of ADM‐2 depicts cell‐free ECM. The decellularization with the use of 0.05% trypsin and 0.02% EDTA solution (as for ADM‐2) was explored by other authors . They examined the efficiency of this procedure for decellularization of porcine heart valves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has also been observed by other authors, for example, observations made by Ng et al (), Rodrigues et al (), or Sorrel and Caplan (). They showed that fibroblasts colonizing the surface of the study ADMs cannot migrate inward towards the ECM structure (Ng et al, ; Rodrigues et al, ; Sorrel & Caplan, ). In order to facilitate fibroblast migration to the interior of the matrices, enzymatic and mechanical methods have been proposed.…”
Section: Discussionsupporting
confidence: 86%
“…Some authors have been evaluating non-enzymatic methods of gingival fibroblasts isolation in vitro for the use in gingival augmentation (6,(10)(11)(12)(13)(14). Gingival fibroblast culture in different matrices has been studied and has shown promising results in soft tissues regeneration (12)(13)(14). Fibroblasts are responsible for the normal growth of the organism and are essential in cases where tissue repairs are necessary, being one of the first cells to appear at injured sites.…”
Section: Discussionmentioning
confidence: 99%